Mobi_Causal a protocol for causal message ordering in mobile computing systems. - Benzaid, Chafika
This paper presents, Mobi_Causal, a new protocol to implement causal ordering in mobile computing systems. The implementation of causal ordering proposed in this paper uses the new timestamping mechanisms proposed by Prakash and Singhal for mobile environments; dependency sequences and hierarchical clocks. Our protocol, compared with previous proposals, is characterized by the elimination of unnecessary inhibition delay in delivering messages while maintaining low message overhead. Our protocol requires minimal resources on mobile hosts and wireless links. The proposed protocol is also scalable and can easily handle dynamic change in the number of participating mobile hosts in the system.
Keywords: Computer Systems Organization; Processor architectures; Other architecture styles; Cellular architecture (e.g., mobile).; Computer communication networks; Network architecture and design; Wireless communication; Network protocols; Protocol architecture (OSI model).; Algorithms; Design; Performance